Milk yield, physico-chemical parameters and fatty acid content from dairy cows fed two types of non-genetically modified soybean cakes - VASILACHI, ANDREEA; CIURESCU, GEORGETA; HÃBEANU, MIHAELA (The Indian Journal of Animal Sciences, 2018)
This study evaluated the inclusion of two types of cakes obtained from non-genetically modified soybean cultivars (cv. Regale, Italy and cv. Onix, Romania; RSBC and OSBC diet, respectively) in dairy cows compound feeds in order to assess their effects on the quantity (yield) and quality (physico-chemical parameters and fatty acids composition) of raw milk.The feeding trial used 16 multiparous Romanian Black Spotted dairy cows, mid-lactation stage, with an initial average milk yield of 18.46 litres/d, assigned to two groups (8 cows each) for 43 days. Milk yield and milk protein were not influenced by the feeding of RSBC or OSBC diet. However, the OSBC diet decreased significantly milk fat content (3.71% vs. 4.08%). Palmitic acid content in milk fat of dairy cows receiving the RSBC diet was significantly lower in comparison with the OSBC diet (30.27% vs. 32.03%). The conjugated linoleic acid content was significantly higher with the RSBC diet, while the total polyunsaturated fatty acids content did not differ among treatments.